(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Nizatidine is a histamine H2-receptor antagonist that inhibits stomach acid production and used in the treatment of peptic ulcer disease and gastroesophageal reflux disease. The main aim of the present investigation was to develop gastro retentive floating microspheres for Nizatidine. These are prepared by ionotropic gelation method with an aim of increasing the gastric residence time and for controlled release. The polymeric mixture of Sodium alginate and HPMCK4, HPMC K15M and HPMC K 100M, was used as polymers. Calcium carbonate was used as the gas forming gent. Prepared Microspheres were characterized for the Micromeretic properties, incorporation efficiency, buoyancy test, SEM analysis, FTIR, and in vitro dissolution studies. The dissolution studies were carried out in 0.1N HCl and the results were applied to various kinetic models. Among the total 18 formulations F17 was optimized. The % yield of F17 formulation was found to be 95.47 ± 0.36%. Based on optical microscopy, the particle size was 50.67 ± 0.13µm. The % buoyancy, % entrapment efficiency and swelling index of F17 formulation was 94.23%, 93.62 ± 0.29% and 92.13 ± 0.17%, respectively. The Cumulative % drug release of F17 formulation was 98.23 ± 5.49% in 12 h when compared with marketed product 95.87 ± 0.31 in 12 h. SEM studies showed the particles were in spherical shape. Based on obtained results, Floating alginate Nizatidine microspheres were of good candidate for targeting to GIT.